Analysis of cervical node metastasis in oral cavity squamous cell carcinoma patients retrospective study and literature comparison - Silva, Leonor Cruz (2023)
Background/Objective: Oral Cavity Cancer is a frequent type of Head and Neck Cancer, associated with high mortality rates worldwide. One of the main prognostic factors for the disease is regional lymph node metastasis that is associated with survival rate reduction by 50%. Reported tumour sites more frequently associated with regional node metastasis vary throughout literature. Therefore, we aimed to conduct a retrospective study that would allow us to identify the relationship between patient and SCC tumour factors with the rate of neck metastasis and compare our data with the conclusions from similar studies. Methods: A retrospective study was conducted in the Oral Medicine and Oncology Consultation of the Stomatology Department from Centro Hospitalar Universitário Lisboa Norte, comprehending patients diagnosed with Squamous Cell Carcinoma between January 2015 and April 2021. As eligibility criteria we considered patients which had clinical charts with complete information including sociodemographic variables, tumour site and disease staging at diagnosis. We excluded tumour sites with only two diagnosed cases, considering bias risk. Three groups were defined according to a clinical/pathological reason. The current research was approved by an independent ethics committee. Results: The sample includes 151 cases, the majority of which were males (≈59%) and with average age at diagnosis (± standard deviation) of 65 ± 13 years-old. Oral tumour sites with highest percentage of cases with clinical positive lymph nodes (cN+) by the time of diagnosis were inferior gingiva (72.7%, n=16), mouth floor (66.7%, n=22), oropharynx (64.7%, n=11), retromolar trigone (58%, n=11) and ventral tongue (57%, n=16). Sites with fewer cases of cN+ were inferior lip (31%, n=4) and superior lip (n=0). Similar results were found in our sample when operated tumors (pN+) were considered: floor of the mouth (65%, n=13), retromolar trigone (63.6%, n=7), inferior gingiva (46.2%, n=6) and ventral tongue (45%, n=9). Tumour sites with fewer pN+ cases were hard palate (25%, n=1), superior gingiva (16.7%, n=1) and inferior lip (0 out of 7 cases). According to Fisher’s exact test there is no statistically significant association (p-value=0.1506) between primary tumour site and cervical node disease (either cN+ or, whenever available, pN+). Conclusions: Our data seem to indicate an association between primary tumour site and N+, being cervical metastasis more frequent when tumour site was posterior and caudally located. Lower lip had the fewer positive lymph nodes, probably correlated with the inclusion in the same group of oral mucosa and skin cancers. Despite these findings, the association was not statistically significant.